Study on the high performance athletes at one mile discipline outdoor all time - Ivan, P.; Gheroghe, D. (Science, Movement & Health, 2017)
Aim. Study bibliography. The collection and tabulation of the following parameters: performances, date of the result, date of birth, citizenship, place of competition and the place of athletes outdoor all time. Processing statistical and mathematical data specified above, regarding the following indicators: number of cases, maximum value, minimum value, amplitude, mode, median, average, quartile 1, 3, quartile difference, dispersion, average of absolute deviation, standard deviation, coefficient of variation and percentage. Evaluation of the results and their interpretation. Methods. As a research method we have used the case study, observation, statistics and graphics. Results. After data processing have resulted 9 summary tables and 4 graphs. Conclusions. The competition is significantly higher in men than in women. To get good results in international competitions men must obtain less than 3:49.36 and women 4:19.16. Women are well represented in the top by 6 athletes, while men have no athlete